Tales, Tunes, and Tassa Drums : Retention and Invention into Indo-Caribbean Music - Manuel, Peter, 1952- (Book collections on Project MUSE., 2015)
"In this study, Peter Manuel discusses Indo-Caribbean music that uses a set of neotraditional music genres to explore how the distinctive nature of the diaspora and its relation to the ancestral homeland have conditioned the trajectories of its music culture. Focusing particularly on tassa drumming, a popular Indo-Trinidadian genre, Manuel traces the roots of neotraditional Indo-Caribbean music genres to North India and explores the ways in which these genres can be seen variously to represent survivals, departures, or innovative elaborations of transplanted genres. He examines music that was carried to Trinidad by Indian immigrants in the early twentieth century, including some forms that died out in India while thriving and evolving in their new world home. Drawing on rich ethnographic work, Manuel reassesses ideas of creolization, retention, and cultural survival in ways that have potentially broad application to other ethnic contexts"--